2014
DOI: 10.1189/jlb.0513281
|View full text |Cite
|
Sign up to set email alerts
|

Rac1 and Rac2 control distinct events during antigen-stimulated mast cell exocytosis

Abstract: The release of preformed mediators from immune cells is through a process described as exocytosis. In mast cells, exocytosis is regulated by several coordinated intracellular signaling pathways. Here, we investigated the role of the hematopoietic-specific Rho GTPase, Rac2, and the ubiquitously expressed Rac1, in controlling mast cell exocytosis. These two isoforms showed equivalent levels of expression in mouse BMMCs. Although Rac1 and Rac2 share 92% sequence identity, they were not functionally redundant, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 64 publications
3
20
0
Order By: Relevance
“…Our findings of significant alterations (rounding) in cells exposed to inhibitors of protein prenylation (simvastatin) suggest that they induce significant defects in the actin cytoskeleton leading to alterations in cell morphology (current studies) and inhibition of GSIS as shown earlier [13, 30]. It should be noted however that studies by Baier et al [31] and Shutes and coworkers [20] demonstrated significant inhibitory effects of EHT 1864 on membrane ruffling in mast cells and lamellipodia formation in U87 MG glioblastoma cells. The observed differences between these studies and our current investigations may, in part, be due to differences in cell types studied and the concentrations of EHT 1864 employed (20 μM in mast cells and 5 μM in glioblastoma cells) [20, 31].…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Our findings of significant alterations (rounding) in cells exposed to inhibitors of protein prenylation (simvastatin) suggest that they induce significant defects in the actin cytoskeleton leading to alterations in cell morphology (current studies) and inhibition of GSIS as shown earlier [13, 30]. It should be noted however that studies by Baier et al [31] and Shutes and coworkers [20] demonstrated significant inhibitory effects of EHT 1864 on membrane ruffling in mast cells and lamellipodia formation in U87 MG glioblastoma cells. The observed differences between these studies and our current investigations may, in part, be due to differences in cell types studied and the concentrations of EHT 1864 employed (20 μM in mast cells and 5 μM in glioblastoma cells) [20, 31].…”
Section: Discussionsupporting
confidence: 66%
“…It should be noted however that studies by Baier et al [31] and Shutes and coworkers [20] demonstrated significant inhibitory effects of EHT 1864 on membrane ruffling in mast cells and lamellipodia formation in U87 MG glioblastoma cells. The observed differences between these studies and our current investigations may, in part, be due to differences in cell types studied and the concentrations of EHT 1864 employed (20 μM in mast cells and 5 μM in glioblastoma cells) [20, 31]. …”
Section: Discussionmentioning
confidence: 99%
“…Rho proteins are central regulators of multiple intracellular processes, and it is interesting how signaling downstream from Rho has evolved to coordinate cytoskeletal remodeling in conjunction with other processes required for immune cell functions. These include many non-cytoskeletal-related functions such as regulation of gene transcription (6972), calcium flux (73, 74), and oxidative burst (7577). …”
Section: Protein Processing In Activated Neutrophilsmentioning
confidence: 99%
“…Vav1 recruitment to the LAT complex in activated mast cells suggests that Rho signaling also has a role in inflammatory processes. Indeed, a role for multiple classes of Rho GTPases in degranulation has been established [9,[13][14][15][16][17]. As central regulators of actin-related morphologies, each member of the Rho GTPase family has a unique role in mediating actin remodeling.…”
Section: Introductionmentioning
confidence: 99%